Metode Pengenalan Puasa Ramadhan Untuk Menguatkan Pemahaman Islami Pada Siswa Sekolah Dasar - Harian Tohadi (GHAITSA : Islamic Education Journal, 2023)
Fasting Ramadan is one of the pillars of Islam, obligatory worship for Muslims who must be commanded by Allah SWT. Fasting not only suppresses thirst and hunger but also takes care of emotions, lust and also behavior from dawn to sun sunset, fasting teaches us tocare socially, get closer to Allah SWT, and have sensitivity to the surroundings. So the children already have to be taught to fast even if you are not a child required for them to implement itHowever, this is done to familiarize children with worship so that children get used to fasting. The formulation of the problem in the research, namely 1) identifying Ramadan fasting as strengthening Islamic understanding, 2) methods that teachers apply to introduce Ramadan fasting, 3) Strategies for controlling children to carry out fasting activities Ramadan. Research methods use qualitative descriptive with interviews, observations and documentation carried out at SDN 71 Bengkulu City with subject teachers and students at school. Data analysis uses triangulation sources. Research result obtained that during the month of Ramadan teachers will fill the school with Islamic activities, such as religious lectures,boarding school express and fill in an activity diary during Ramadan to control children's activities at home, such as prayer,read Al-Qur’an, prayers tarawih, listentalk, and how many fasts have been fulfilled.